2007
DOI: 10.1016/j.jbiomech.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of the double rocker sole shoe: Gait kinematics and kinetics

Abstract: The use of footwear with contoured soles is common in treatment and care of patients with diabetes; these rocker sole shoes are designed to alleviate loading in key areas on the plantar surface of the foot, reducing pressure in key areas and alleviating pain and potential soft tissue damage. While investigations of pressure changes have been conducted, no quantitative study to date has addressed the three-dimensional kinematic and kinetic changes that result from using these shoes. Forty (40) subjects were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 30 publications
1
24
1
Order By: Relevance
“…Later in stance, the increased dorsiflexion of the foot observed in the Twin Shoe condition indicates a better rollover process. These results are in agreement with the observations of Long et al [12] who reported an increased dorsiflexion at heel contact and during mid stance when wearing double rocker diabetic shoes bilaterally. Therefore, it could be suggested that using the Twin Shoe has nearly the same effect on foot kinematics as an elevated medical shoe.…”
Section: Discussionsupporting
confidence: 93%
“…Later in stance, the increased dorsiflexion of the foot observed in the Twin Shoe condition indicates a better rollover process. These results are in agreement with the observations of Long et al [12] who reported an increased dorsiflexion at heel contact and during mid stance when wearing double rocker diabetic shoes bilaterally. Therefore, it could be suggested that using the Twin Shoe has nearly the same effect on foot kinematics as an elevated medical shoe.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have investigated the effect of improved shoes such as the rocker sole shoe, SACH heel shoe, and heelless shoe, which was made to improve walking stability and reduce joint load [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…From a biomechanical point of view, the goals in designing rocker-soled shoes include: (1) the curved surface at the front of the sole primarily functions to reduce stress and shear force in the push-off phase, reduce excessive bending of the metatarsal-phalangeal joint, and increasing forward thrust [1, 4, 8, 15]; (2) the curved surface at the rear of the sole primarily functions to reduce impact force during heel strike, and protects the heel bones and ligaments [1, 2]; (3) the flat middle part primarily supplies stability and support in midstance, as well as level plantar force [1, 2, 4, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%